Development and characterization of a fully human antibody targeting SCF/c-kit signaling - Kim, Jin Ock; Kim, Ha Neul; Kim, Kwang Hyeok; Baek, Eun Ji; Park, Jeong Yang; Ha, Kyungsoo; Heo, Deok Rim; Seo, Min Duk; Park, Sang Gyu (International Journal of Biological Macromolecules, 2020)
CD117/c-kit, a tyrosine kinase receptor, plays a critical role in hematopoiesis, pigmentation, and fertility. The overexpression and activation of c-kit are thought to promote tumor growth and have been reported in various cancers, including leukemia, glioblastoma and mastocytosis. To disrupt the SCF/c-kit signaling axis in cancer, we generated a c-kit antagonist human antibody (NN2101) that binds to domain 2/3 of c-kit. This completely blocked the SCF-mediated phosphorylation of c-kit and inhibited TF-1 cell proliferation, erythroleukemia. In addition, the examination of binding affinity using surface plasmon resonance (SPR) assay showed that NN2101 can bind to c-kit of monkeys (KD = 2.92 × 10−10 M), rats (KD = 1.68 × 10−6 M), mice (KD = 11.5 × 10−9 M), and humans (KD = 2.83 × 10−12 M). We showed that NN2101 does not cause antibody-dependent cell-mediated cytotoxicity and complement-dependent cytotoxicity. The immunogenicity of NN2101 was similar to that of bevacizumab. Furthermore, the crystal structure of NN2101 Fab was determined and the structure of NN2101 Fab:c-kit complex was modeled. Structural information, as well as mutagenesis results, revealed that NN2101 can bind to the SCF-binding regions of c-kit. Collectively, we generated a c-kit neutralizing human antibody (NN2101) for the treatment of erythroleukemia and characterized its biophysical properties. NN2101 can potentially be used as a therapeutic antibody to treat different cancers.
Keywords: Animals; Antibodies, Neutralizing; Antineoplastic Agents, Immunological; Binding Sites, Antibody; Cell Proliferation; Cells, Cultured; Epitopes; Haplorhini; HEK293 Cells; Humans; Mice; Proto-Oncogene Proteins c-kit; Rats; Antibody; c-kit; Cancer; Crystal structure; SCF